2016
DOI: 10.1039/c6ra04569c
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Ag–Cu alloy nanoparticles as a highly active catalyst for the enamination of 1,3-dicarbonyl compounds

Abstract: Bimetallic Ag–Cu alloy nanoparticles were obtained via a simple co-reduction method, which exhibited significantly improved activity for the synthesis of β-enaminones and β-enaminoesters compared with their monometallic counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 91 publications
4
42
0
Order By: Relevance
“… Scheme summarizing different classes of multi‐metallic nanostructures as well as corresponding examples of laser‐generated nanomaterials. In the 3 rd row TEM‐EDX pictures are shown for AgAu (fundamentals), NiMo (electrocatalysis), PtCo (electrocatalysis), AuFe (fundamentals [58] , reduction reactions), AgCu (fundamentals [202] , enamination reaction) and PtCuCo (electrocatalysis). TEM‐EDX picture of AgAu adapted with permission from Ref.…”
Section: Laser‐based Materials Design: Multi‐elemental Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“… Scheme summarizing different classes of multi‐metallic nanostructures as well as corresponding examples of laser‐generated nanomaterials. In the 3 rd row TEM‐EDX pictures are shown for AgAu (fundamentals), NiMo (electrocatalysis), PtCo (electrocatalysis), AuFe (fundamentals [58] , reduction reactions), AgCu (fundamentals [202] , enamination reaction) and PtCuCo (electrocatalysis). TEM‐EDX picture of AgAu adapted with permission from Ref.…”
Section: Laser‐based Materials Design: Multi‐elemental Nanoparticlesmentioning
confidence: 99%
“…[213] Consequently, for 3 particles observed in this study, the authors found a low number of carbon shells in case of smaller nanoparticles, and vice versa. [213] Recently, this correlation was [61] (fundamentals), NiMo [32] (electrocatalysis), PtCo [192] (electrocatalysis), AuFe [58] (fundamentals [58] , reduction reactions [207] ), AgCu [202] (fundamentals [202] , enamination reaction [208] ) and PtCuCo [205] (electrocatalysis). TEM-EDX picture of AgAu adapted with permission from Ref.…”
Section: Carbon-covered Core-shell Nanostructuresmentioning
confidence: 99%
“…In comparison, absorption peak at around ∼550 was observed for Cu nanoparticle. The absorption peak of bimetallic alloy Ag 1 ‐Cu 1 nanoparticles exhibits at ∼435 nm which lies in between the Ag and Cu monometallic nanoparticles . For Cu@Ag core‐shell nanoparticles the band at ∼410 nm corresponds to surface plasmon peak for Ag nanoparticles.…”
Section: Resultsmentioning
confidence: 98%
“…TEM micrograph of alloy Ag 1 ‐Cu 3 nanoparticle is presented in Figure S1, where spherical particle are observed with an average particle size of 15±2.5 nm. The crystalline nature was studied by SAED analysis which shows ring like structure with fcc phase of Ag and Cu . The EDS analysis shows the existence of Ag and Cu with 1:3 ratios.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation